DETERMINATION OF UREA USING P-N,N-DIMETHYLAMINOBENZALDEHYDE: SOLVENT EFFECT AND INTERFERENCE OF CHITOSAN - Juan D. Giraldo; Bernabé L. Rivas (Journal of the Chilean Chemical Society, 2017)
An optimized spectroscopic methodology for the quantification of urea using p-dimethylaminobenzaldehyde (DMAB) as a derivatizing reagent is proposed to avoid changes in reproducibility caused by aging of acidic DMAB solutions, and the unintended use of different solvents. Four solvents; ethanol, methanol, 2-propanol and acetonitrile are evaluated. Acetonitrile has never been reported for the determination of urea with DMAB, and it is found to be the best medium for the quantification of urea due to its aprotic nature. The use of acetonitrile allows a more stable reaction system, which results in a faster urea quantification, less acid consumption and a more sensitive spectroscopic method. Taking into account that polymer matrices of chitosan are being used recently to develop controlled release fertilizers of urea, a complementary study is carried out to determine any interference by released chitosan macromolecules with different molecular mass and degree of deacetylation in the optimized system. The results show no appreciable changes in the sensitivity and accuracy of the methodology being other available application of this work.